Green Organizational Culture dan Green Intellectual Capital sebagai Determinan Keberlanjutan Bisnis pada Perusahaan Manufaktur Indonesia - Ketut Tanti Kustina; Kadek Putri Maharani (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2026)
In the current era of globalization and increasingly rapid technological developments, awareness of the importance of environmental sustainability is increasing and has become a crucial issue that is increasingly receiving attention in various parts of the world. Management awareness of ESG is very important to improve business sustainability, because it can increase innovation, reputation and supply chain efficiency, as well as create long-term value for stakeholders, so one effective strategy to achieve business sustainability is to implement a Green Organizational Culture and Green Intellectual Capital. The aim of this research is to determine the influence of Green Organizational Culture and Green Intellectual Capital on business sustainability. The data used is secondary data which will be obtained from the distribution of annual financial reports. The number of samples used in this research is 225 manufacturing company data for the 2022-2023 period. The data collection technique used is through the Indonesian Stock Exchange (BEI). The analysis technique uses multiple linear regression. The results of this research are that Green Organizational Culture has a positive and significant effect on business sustainability. Green Intellectual Capital has a positive and significant effect on business sustainability.